DECISION SUPPORT SYSTEM FOR PURCHASING OF MIRRORLESS CAMERA USING WEIGHTED PRODUCT METHOD - Ayu Manik Martawiharjo; Melan Susanti; Mari Rahmawati (Jurnal Techno Nusa Mandiri, 2022)
A mirrorless camera is a camera that does not have a mirror or a pentaprism with the size and workpiece of a compact camera, but has an equivalent capability to a DSLR camera. There are several mirrorless camera manufacturers widely known in the market, among others: Canon, Sony, Fujifilm, Nikon, Olympus, and Panasonic with the advantages of each manufacturer's specifications highlighted to enhance the attractiveness of consumers. With many types of mirrorless cameras in the market, many consumers are still confused in choosing which mirrorless camera is right and suited to their needs. Therefore, it takes a decision support system for the selection of mirrorless cameras using the weighted product method that can generate decisions about mirrorless cameras that comply with the selection of consumer criteria. The criteria used in this study are price, sensor size, megapixel, maximum ISO, and LCD. The results of this study show that the alternative mirrorless camera which has the highest value is the Olympus PEN E-PL9 camera with a value of 0.148.